Efficiency of Islamic banks in GCC countries: International Evidence using the Stochastic Frontier Approach (SFA) - Boyakov, Ziyoratsho (2013)
This study estimates and compares the efficiency of 18 full-fledged Islamic banks in 5 of Gulf Cooperation Council countries. The time period between 2006 and 2011 is selected in order to capture the impact of Global Financial Crisis on Islamic banks. Moreover, this paper uses five environmental variables to control cross-country differences in the environment in which banks operate. The study employs SFA distance functions and intermediation approach to measure the technical and cost efficiency of these banks. The results suggest that, on average, the technical efficiency scores widely fluctuated between 62% and 95%. The low scores in 2007 and 2008 are attributed to the fact that GCC countries were among the countries that have suffered from the financial crisis. The banks in Saudi Arabia and Qatar performed better than the other GCC countries banks due to their natural economies of scale and economies of scope. In contrast, U.A.E. banks had the lowest efficiency scores because of the significant exposure to construction and real estate sector. The results also suggest that increase in Loans and operating expenses have positive impact, while increase in other operating income and personal expenses have negative impact on banks efficiency level. However, there is substantial room for improvement in cost efficiency of these Islamic banks.